The Use of Gamification Methods Through Thematic Activities to Enhance Vocabulary Mastery of Fifth Grade Students at SDN 006 Palembang - Via Oktavita; Hartini Agustiawati; Ressy Novasyari; Na'imatul Husni (Utan Kayu Publishing, 2025)
This study examines the effectiveness of gamification methods integrated with thematic activities in enhancing the vocabulary mastery of fifth-grade students at SDN 006 Palembang. The research was motivated by students’ common challenges in memorizing and retaining vocabulary. The objective was to determine whether there is a significant difference in vocabulary achievement between students taught using gamification and those taught through conventional methods. A quantitative approach with a pre-test–post-test experimental design was applied. The participants were two fifth-grade classes: class 5B as the experimental group (N = 29) and class 5A as the control group (N = 30). A 50-item vocabulary test served as the main instrument. Due to the non-normal distribution of data, the Wilcoxon Signed-Rank Test was used for within-group analysis, and the Mann-Whitney U Test was used for between-group analysis.The results showed significant improvement in both groups from pre-test to post-test. However, the experimental group achieved a higher post-test mean rank (34.79) than the control group (25.37), with a statistically significant difference (p = .033). These findings indicate that the use of gamification integrated with thematic activities has a significant positive impact on improving vocabulary mastery among fifth-grade students.